Implementation of the Omron CP1E PLC on Continuous Automatic Plastic Shredding Machine Prototype - Adam, Mochammad Rizki; Wisaksono, Arief; Sulistiyowati, Indah; Ayuni, Shazana Dhiya (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Currently, the industrial world cannot be separated from plastic waste, one of which is sheet plastic waste, where this type of waste is very difficult to decompose in the soil, so it is necessary to recycle plastic waste by crushing it and then melting it in processing media such as plastic injection machine. Sheet plastic is usually processed through a shredding or crushing process using a plastic cutting machine. Most of the shredding machines in the industrial world still add plastic waste manually, with the shredding machine components still using a single motor which is used to drive the plastic shredding machine. To solve the above problem by adding several components to the plastic waste shredding machine so that it can be operated automatically using an Omron CP1E PLC, adding a blower motor and a traction motor that uses an inverter or PWM (Pulse Width Modulation) which functions to pull the remaining sheets. The plastic is then shredded by a grinder motor and the shredded results are moved by a blower motor to a special waste bin. This research applies research and development methods with a focus on designing a plastic chopping machine that operates automatically with a continuous system, based on a PLC using CX-One software. This research proves that automatic plastic shredding machines can increase efficiency, work safety and reduce production costs.